HAEMATOLOGICAL PROFILES OFASIAN ELEPHANTS FED WITH PROBIOTIC FEED ADDITIVES - Dharmendra Chharang; Sheela Choudhary (Exploratory Animal and Medical Research, 2022)
Haematological profiles indicate the health status and ability to resist infections as it plays a significant role in the nutritional, physiological, and pathological state of animals. Supplementation of intestinal microflora with probiotic microbiota was proven to help to treat infections. So an experiment was conducted to determine the effect of probiotic feed additives on haematological profiles in 18 captive Asian elephants for two months. The experimental probiotics; Lactobacillus acidophilus and Saccharomyces cerevisiae, were supplemented @ 1 gm 1 × 109 CFU /gm for every 50 kg body weight per day to all the elephants of Lacto (T2) and Sac (T3) groups respectively, whereas no probiotic was given to the Control (T1) group. Haematological constituents, namely (i) red blood cell indices, white blood cell indices, and platelet cell indices were analyzed. The observed values of red blood cell indices revealed a non-significant effect among the groups. A highly significant (p < 0.01) effect was observed in the differential leukocyte count, which shows signs of an immune-stimulatory effect. Significant (p < 0.05) effect of treatment was recorded on mean platelet volume. The addition of probiotic feed additives did not affect the physiological health of the captive Asian elephants since the parameters studied were well within the normal physiological range of a healthy animal.